Albumin for patients with acute large-vessel occlusive stroke undergoing endovascular therapy (ARISE): the protocol of a randomized double-blind trial - Yuanyuan Liu; Xiao Dong; Xuehong Chu; Zhengfei Ma; Tingyu Yi; Tingyu Yi; Changming Wen; Yifeng Liu; Jun Sun; Jing Xu; Wenbo Li; Lei Yang; et al. (Frontiers in Neurology)
BackgroundAlbumin is a multifunctional plasma protein that is mainly synthesized in the liver and may play a neuroprotective role in treating acute ischemic stroke (AIS). The efficacy of albumin in patients with AIS receiving reperfusion therapy remains unknown.MethodsARISE is a multicenter, randomized, double-blind, placebo-controlled, phase 2 study. We will recruit 134 patients aged 18–80 years with AIS due to large-vessel occlusion in the anterior circulation, within 24 h of symptom onset, with an Alberta Stroke Program Early CT Score of 3–10 points and an infarct core volume of ≤100 mL at baseline. Eligible patients will be randomly assigned, on a 1:1 ratio, to undergo endovascular therapy (EVT) and receive albumin therapy (0.5 g/kg; intravenous injection) once daily for 4 days or to undergo EVT and receive placebo therapy once daily for 4 days. The primary efficacy outcome is the change in infarct volume from baseline to day 5.ConclusionThe ARISE trial will provide valuable evidence on the efficacy and safety of albumin in patients with AIS receiving EVT.Clinical trial registrationwww.clinicaltrials.gov, NCT06538844.